(untitled) (Multidisciplinary Journal of Science and Technology, 2026)
The transition from authoritarian didactic frameworks to highly responsive, individualized pedagogical architectures requires a profound restructuring of early childhood support systems. This study evaluates the precise psychopedagogical outcomes of implementing a strict person-centered educational model compared to conventional uniform instruction. A prospective, quasi-experimental analysis was conducted involving 132 neurotypical children (aged 4–6 years). Subjects were stratified into a conventional instructional cohort (n=64) and a targeted experimental cohort (n=68) integrated into a person-centered support system emphasizing autonomous play schemas and affective scaffolding over 6 months. Empirical data indicate that adult-centric modalities frequently induce subclinical psychological resistance. The targeted cohort demonstrated a 44.2% acceleration in executive self-regulation, with standardized Leuven Well-being scores rising from a baseline of 3.2 ± 0.4 to 4.8 ± 0.2 (p = 0.007). Conversely, the conventional group exhibited persistent plateaus in creative problem-solving and a higher incidence of cortisol-mediated behavioral dysregulation. The dynamics of the observed results suggest that pedagogical support cannot function as a generalized intervention. Comprehensive early education frameworks must actively systematize person-centered principles, utilizing the child’s intrinsic interests as primary vectors for cognitive development to forge resilient psychological architecture.